Serum amyloid A promotes LPS clearance and suppresses LPS‐induced inflammation and tissue injury. (20th August 2018) - Cheng, Ni; Liang, Yurong; Du, Xiaoping; Ye, Richard D
Abstract: Lipopolysaccharide (LPS) is a major microbial mediator for tissue injury and sepsis resulting from Gram‐negative bacterial infection. LPS is an external factor that induces robust expression of serum amyloid A (SAA), a major constituent of the acute‐phase proteins, but the relationship between SAA expression and LPS‐induced tissue injury remains unclear. Here, we report that mice with inducible transgenic expression of human SAA1 are partially protected against inflammatory response and lung injury caused by LPS and cecal ligation and puncture (CLP). In comparison, transgenic SAA1 does not attenuate TNFα‐induced lung inflammation and injury. The SAA1 expression level correlates inversely with the endotoxin concentrations in serum and lung tissues since SAA1 binds directly to LPS to form a complex that promotes LPS uptake by macrophages. Disruption of the SAA1‐LPS interaction with a SAA1‐derived peptide partially reduces the protective effect and exacerbates inflammation. These findings demonstrate that acute‐phase SAA provides innate feedback protection against LPS‐induced inflammation and tissue injury. Synopsis: High‐level production of serum amyloid A is a hallmark of acute‐phase response. Human SAA1 interacts with LPS, which promotes LPS clearance and reduces serum endotoxin levels in SAA1 transgenic mice. Transgenic expression of human SAA1 in mice simulates SAA production in acute‐phase response. SAA1 attenuates lung inflammation, improves survival and reduces serum endotoxin levels in mice receiving CLP or LPS. SAA1 forms a complex with LPS and promotes LPS uptake by macrophages. Disruption of the SAA1‐LPS interaction abrogates the protective effect of SAA1. Abstract : High‐level production of serum amyloid A is a hallmark of acute‐phase response. Human SAA1 interacts with LPS, which promotes LPS clearance and reduces serum endotoxin levels in SAA1 transgenic mice.